The Exploring West Sumatra E-Book: Enhancing Early Reading Skills and Literacy in Early Childhood Education - Nilawati; Nurhafizah (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Early reading skills in early childhood are often a challenge, especially in preparing them for the next level of education. Therefore, interesting, effective, and relevant learning media are needed with technological developments. This study aims to develop the e-book Let's Get to Know West Sumatra as a learning media that can improve early reading skills and foster a love of books in the Merdeka curriculum. This e-book is designed by presenting relevant letters and vocabulary to support early childhood literacy. This study uses the ADDIE development method which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were children at the Integrated Islamic Kindergarten. Meanwhile, the object of this research is the Development of an E-Book on Getting to Know West Sumatra in Kindergarten. The research instruments include validity, practicality, and effectiveness tests. Furthermore, the data was analyzed to find the results of the research that had been conducted. The results of the study showed that the e-book Let's Get to Know West Sumatra is very valid, practical, and effective in improving early reading skills and literacy in early childhood aged 5-6 years. With topics that are close to children and the use of the surrounding environment, this e-book allows children to repeat their favorite stories, which contributes to strengthening reading skills and increasing self-confidence. The innovation of the e-book Let's Get to Know West Sumatra has implications for adding variations of learning media that can help improve early reading skills in early childhood.